2023
DOI: 10.1088/1741-2552/accd9b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of EEG–EMG coupling detection using corticomuscular coherence with spatial–temporal optimization

Abstract: Corticomuscular coherence (CMC) is widely used to detect and quantify the coupling between motor cortex and effector muscle. It is promisingly used in human-machine interaction (HMI) supported rehabilitation training to promote the closed-loop motor control for stroke patients. However, suffering from weak coherence features and low accuracy in contingent neurofeedback, its application to HMI rehabilitation robot is currently limited. In this paper, we propose the concept of spatial-temporal CMC (STCMC), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Motor impairment emerges as the most common consequence of stroke; more than 80% of stroke survivors have acute impairment, and more than 50% have chronic impairment ( 2 ). Currently, advanced neurotechnologies, including but not limited to rehabilitation robotics ( 3 ), brain machine interaction (BMI) ( 4 , 5 ), brain stimulation ( 6 ), functional electrical stimulation (FES) ( 7 ), aimed at restoring motor function have attracted huge attention from professionals and public. Recent clinical studies on these approaches have shown promising results ( 8 ).…”
mentioning
confidence: 99%
“…Motor impairment emerges as the most common consequence of stroke; more than 80% of stroke survivors have acute impairment, and more than 50% have chronic impairment ( 2 ). Currently, advanced neurotechnologies, including but not limited to rehabilitation robotics ( 3 ), brain machine interaction (BMI) ( 4 , 5 ), brain stimulation ( 6 ), functional electrical stimulation (FES) ( 7 ), aimed at restoring motor function have attracted huge attention from professionals and public. Recent clinical studies on these approaches have shown promising results ( 8 ).…”
mentioning
confidence: 99%